Factor by grouping: ab-3a+4b-12

### 2 Answers | Add Yours

The expression ab-3a+4b-12 has to be factored.

ab-3a+4b-12

= a(b - 3) + 4(b - 3)

= (a + 4)(b - 3)

**The factored form of ab-3a+4b-12 = (a + 4)(b - 3)**

ab-3a+4b-12 just find what they have in common

(ab-3a)(4b-12)

a(b-3) 4(b-3)

(b-3) (a+4) you can go even father if you want and get the main answer by setting the parenthesis equal to zero.

(b-3) = 0

b=3

a+4=0

a=-4

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes